Leaf morphology, photosynthesis and pigments change with age and light regime in savin juniper. (15th August 2021) - Zhang, J.‐L.; Li, X.‐G.; Xu, X.‐H.; Chen, H.‐P.; Li, Y.‐L.; Guy, R. D.
Abstract: Savin juniper is an excellent species for desertification control in arid and semi‐arid areas, where it typically establishes under the protection of nurse plants. Ultimately, established plants emerge into full light as they grow, and this transition is accompanied by an increase in the preponderance of scale‐like versus needle‐like leaf forms. To test how age and variable light environments affect shade tolerance in savin juniper, we established a pot study under field conditions, with two age cohorts (1‐ and 4‐year‐old rooted scions) and three light regimes (10%, 50% and 100% light transmittance). We measured growth, leaf parameters, photosynthesis, chlorophyll fluorescence and foliar pigments on a monthly basis (seven growing months per year, from 2015 to 2017). Overall, there was little interaction among all variables, and both cohort and light regime had significant effects. Leaf form and spacing varied continuously, tending towards shorter, more closely spaced and more appressed scale leaves with higher dry leaf mass per area in older plants or under higher light. There were no clear age‐related patterns in carotenoids but both cohort and light had significant effects on gas exchange and chlorophyll fluorescence variables. We conclude that savin juniper shows an intermediate tolerance to shade that changes with growth in that younger plants were less tolerant of full sun than older plants, consistent with its reliance on nurse plants for ultimate establishment in the open. Abstract : Age and light affect growth, leaf form, photosynthetic rate and photoinhibition of savin juniper, an evergreen shrub‐tree species, and 1‐year‐old plants are more shade tolerant than 4‐year‐old plants.